المؤسسات الصغيرة والمتوسطة ودورها في ترقية الصناعة الغذائية في الجزائر - مخبي ،الصافية; العايب ،ياسين (جامعة الوادي University of Eloued, 2024)
عملنا من خلال هذه الدراسة إلى ابراز أهمية المؤسسات الصغيرة والمتوسطة في الجزائر خصوصا بعد المجهودات التي قامت بها الدولة لتشجيع المقاولاتية ومدى مساهمتها في ناتج قطاع الصناعة الغذائية، من أجل ذلك حاولنا الوصول إلى واقع تطور المؤسسات الصغيرة والمتوسطة والعاملة في قطاع الصناعة الغذائية وأثرها على بعض المتغيرات الاقتصادية كالناتج الخام والقيمة المضافة، لكن توصلنا إلى أنه ورغم المجهودات الكبيرة من طرف الدولة إلا أن المؤسسات الصغيرة والمتوسطة ساهمت بقدر ضئيل جدا في ترقية الصناعة الغذائية، نظرا لهيمنة الأعمال الحرة عليها كما أنها تساهم بنسبة صغيرة جدا في الناتج الخام وخلق القيمة This study aimed to emphasize the significance of small and medium-sized enterprises (SMEs) in Algeria, particularly in light of the government's efforts to promote entrepreneurship. It also sought to evaluate the contribution of this sector to the development of the food industry. We analyzed the growth of SMEs within the food industry in Algeria and assessed their impact on certain economic variables such as gross output and value added, However we found that despite significant government efforts, SMEs They have made only a minor contribution to the development of the food industry, primarily due to the dominance of informal businesses within the SME sector, which has also resulted in a limited impact on gross output and value creation.
Small and Medium Enterprises and Their Role in Upgrading the Food Industry in Algeria
Keywords: الصناعة الغذائية; المؤسسات الصغيرة; الناتج الخام; القيمة المضافة; الاقتصاد الجزائري; Food industry; Small and medium enterprises; raw output; added value